Pitheciid research comes of age: Past puzzles, current progress, and future priorities. Issue 5 (11th October 2015) - Barnett, Adrian A.; Boyle, Sarah A.; Thompson, Cynthia L.
Abstract : For a long time, members of the Pitheciidae were among the least studied of all Neotropical primates. But times have changed. Here, we trace the trajectory of this change and show how the articles in this special edition illustrate new knowledge and developments in our understanding of pitheciid ecology, behavior, and conservation. We propose new directions and priorities for future research, especially to ensure the effective conservation of pitheciids, and demonstrate how studies of this family are now the focus of hypothesis‐driven research that not only allows the details of this family's biology to be explored, but will allow its biology to be compared with other primate lineages. Am. J. Primatol. 78:487–492, 2016. © 2015 Wiley Periodicals, Inc.